(untitled) (Socio-economic relations in the digital society, 2019)
The article analyzes the current state of the organization and functioning of banks in the payment system. Investigated the problems and prospects for auditing transactions with payment cards. Depending on the used methodological approaches to evaluating the economic efficiency of operations with payment cards banks characterized by efficiency of operations and feasibility defi ned market segments expand payment cards. In view, experienced some problem to processing methods of analysis and audit and the effectiveness of these operations. All of that will be help to evaluate resource consumption, complexity of operations and investments for Th is requires an integrated, systematic approach to the methods of economic analysis and audit in this area.the introduction of new card products and technologies.